Developing a model and instrument to measure the resilience of critical infrastructure sector organisations. (2018) - Hatton, Tracy; Brown, Charlotte; Kipp, Robert; Seville, Erica; Brouggy, Peter; Loveday, Michelle
Societies are highly reliant on uninterrupted critical infrastructure services. Until recently, the focus has been on the physical resilience of hard assets such as pipes, cables and buildings. Attention is now also turning to a systems approach, considering the capabilities of, and interconnections between, the organisations responsible for developing, maintaining and running those infrastructures. This paper draws on existing research into organisational resilience to develop a model and measurement instrument for whole of sector resilience for selected critical infrastructure sectors, in order to identify sector resilience strengths and weaknesses, and to develop and evaluate the effectiveness of their resilience strategies and investments. The model is intended as a 'conversation starter' to prompt further research on how critical infrastructure organisations can best address their significant co-dependencies to ensure the overall sector's ability to survive and thrive, even in times of crisis.